PENINGKATAN PENGETAHUAN DAN KEMAMPUAN ORANGTUA DALAM MENANAMKAN NILAI TAUHID PADA ANAK USIA DINI - Rohita; Rizqi Maulida (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract: The low level of parental knowledge regarding the value of monotheism in early childhood especially in introducing the Prophet Muhammad, the family of the Prophet Muhammad, and the companions of the Prophet Muhammad resulted in the low ability of parents to carry out family religious functions in the South Tangerang area. Based on this, the purpose of this community service activity is to increase the knowledge and ability of parents to instill tauhid values ​​in introducing the Prophet Muhammad, the family of the Prophet Muhammad, and the companions of the Prophet Muhammad. The solutions provided were in the form of training with a series of activities on knowledge transfer, workshops, and simulations of the story of the Prophet Muhammad, the family of the Prophet Muhammad, and friends of the Prophet Muhammad to the children. The results of the activity indicate that there was an increase in knowledge which amounts to 62.12%. While the ability of parents to instill tauhid values ​​seen from the ability of parents to convey stories to children also increased, which amounted to 77.27%.             Abstrak:Rendahnya pengetahuan orangtua mengenai nilai tauhid pada anak usia dini terutama dalam mengenalkan Rasulullah SAW, keluarga Rasulullah SAW, dan sahabat Rasulullah SAW mengakibatkan rendahnya kemampuan orangtua dalam melaksanakan fungsi keagamaan keluarga di wilayah Tangerang Selatan. Berdasarkan hal tersebut, tujuan dilakukannya kegiatan pengabdian masyarakat ini adalah meningkatkan pengetahuan serta kemampuan orangtua untuk menanamkan nilai tauhid dalam mengenalkan Rasulullah SAW, keluarga Rasulullah SAW, dan sahabat Rasulullah SAW. Solusi yang diberikan berupa pelatihan dengan rangkaian kegiatan transfer knowledge, workshop, dan simulasi penyampaian kisah Rasulullah SAW, keluarga Rasulullah SAW, dan sahabat Rasulullah SAW kepada anak. Hasil kegiatan menunjukkan bahwa terjadi peningkatan pengetahuan sebesar 51.33%. Sementara kemampuan orangtua dalam menanamkan nilai tauhid yang dilihat dari kemampuan orangtua menyampaikan kisah-kisah kepada anak juga mengalami peningkatan, yaitu sebesar 77.27%.